Developing CCU Instructional Materials Integrated with Local Cultures in Improving EFL Learners’ Communicative Competences - Aristia, Erni Sona; Siswantara, Eka; Ismiati, Ismiati (JOLLT Journal of Languages and Language Teaching, 2025)
Cross-cultural understanding (CCU) is increasingly recognized as a crucial element in teaching English as a Foreign Language (EFL), as it not only enhances linguistic proficiency but also equips learners with the ability to navigate cultural nuances and social contexts. In response to this need, the current study developed instructional materials that integrate local cultural elements into CCU courses, aiming to improve EFL learners’ communicative competences. Employing a Research and Development (R&D) approach, the study followed three stages: define, design, and develop. The resulting product was a prototype of instructional materials tailored to teach CCU effectively. The materials underwent rigorous quality assessments through expert validation and field testing in English classes. The findings revealed that the instructional materials are valid and appropriate for teaching CCU, demonstrating a significant positive impact on learnersâ€™ communicative competences. Specifically, the integration of local cultural contexts fostered a deeper understanding of both target language use and cross-cultural interaction, bridging gaps between learners’ cultural frameworks and English-communication contexts. The implication of this study underscores the importance of incorporating local cultural elements in CCU courses, highlighting that such integration not only contextualizes language learning but also enhances learnersâ€™ engagement and adaptability in real-world communication. By promoting culturally responsive teaching, these materials provide a model for developing context-sensitive EFL curricula that address global communication demands while preserving local cultural identity.